A New Analysis Protocol for the Studying of Ancient Terracottas - Battini, Laura (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2021)
Pre-classical Ancient Near Eastern clay figurines and plaques still remain essentially connected to an iconographic analysis. This article aims to renew the methodology of one of the richest group of ancient artefacts in number and meaning: terracottas.